Physical characteristics of pumpkin seeds (Cucurbita moschata) grown in Santa Lucía Atlántico, Colombia (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2024)
The physical properties of oilseeds and other grains are affected by numerous factors such as seed size, variety and moisture. Likewise, these properties are essential for the design of drying, aeration, storage and treatment equipment. The objective of the study was to characterize the physical properties of pumpkin seed (Cucurbita moschata) for crop improvement in Santa Lucia Atlántico, Colombia. The weight of 100 seeds, dimensions, actual density, bulk density, porosity, swelling capacity and water holding capacity of pumpkin seed with and without shell were measured; a 2-factor ANOVA with 3 repetitions was applied to the data obtained. The results of the study revealed that the weight of 100 seeds and the dimensions show more variable values in terms of shelled and shelled seeds. While real density, bulk density, porosity and swelling capacity present significant minor differences between samples. Finally, the only parameter that showed no statistically significant differences was the water holding capacity, which is similar for shelled and shelled seeds. In conclusion, the shell represents about 30% of the total pumpkin seed and has a great influence on physical properties. Likewise, these properties change according to the variety, humidity and stage of maturation of the seed.
Keywords: seed; pumpkin; physical characteristics; porosity; water retention capacity